KEWAJIBAN NEGARA DALAM PEMENUHAN AKSES TERHADAP AIR - Teguh Iman Sationo (Pusat Studi HAM dan Humaniter Fakultas Hukum Universitas Widya Mataram, 2022)
Water is a basic need of human being, no one can live without water and it has no substitution. Water is a a requirement of adequate living standard for the health and well-being of all human being..The current problem is the availability of water in fulfill the human need is decreased. On the one hand there is the view that water is a commodity while the other side said that water is a social good.. The right to water implies that everyone should have access to water without discrimination. The state’s role is indispensable when people are not in the same position in getting water, the differences position of people can occur not only a problem of economic inequality, but also the specific natural conditions in a certain region. Such differences make some parts of society difficult to gain access to water, and in this situation, the presence of the state is strong required.